Anti-Corruption Policy in Ukraine During the War with Russia - Astramowicz-Leyk, Teresa (PRAWO i WIĘŹ, 2023)
Anti-corruption policy indicates the maturity of the political system in conditions of uncertainty. In times of war, anti-corruption principles and mechanisms become decisive for achieving victory over the enemy and successfully reviving the state. According to the authors, Ukraine should urgently resolve corruption issues in such sectors (institutions) as health care, judiciary, prosecutor’s office and law enforcement agencies, customs and tax service, state regulation of the economy and interaction between the state and the private sector, and activities of political parties. Moreover, in conditions of Russia’s armed aggression against Ukraine, solving corruption issues in the defence sector and preventing corruption in state-owned enterprises, considering the significant damage caused by corruption in this sector, is of primary importance.